Navigating the Waters of Pollution: Understanding Distinctive Factors and Solutions for Clean Water Sustainability - Awad, Salah Adeen I; Alwitwat, Rajah Miftah Abdullah (Stallion Journal for Multidisciplinary Associated Research Studies, 2022)
Water pollution presents a critical challenge to global sustainability, threatening ecosystems and human health alike. This paper explores the intricate factors contributing to water pollution and evaluates viable solutions for ensuring clean water sustainability. Analyzing industrial discharge, agricultural runoff, and urbanization, the research identifies key pollutants and their sources, offering a comprehensive understanding of the current landscape. Through a blend of chemical analysis and case studies, the findings highlight the most pervasive contaminants and their regional variations. The discussion underscores the necessity of integrating technological innovations, policy reforms, and community-driven initiatives to combat pollution effectively. Recommendations emphasize the importance of advanced water treatment methods, stringent regulatory frameworks, and widespread educational efforts to foster community engagement and accountability. By presenting both the challenges and actionable solutions, this study aims to inform and inspire stakeholders at all levels to prioritize and implement measures for a sustainable clean water future.